Stochastic Principal Parametric Resonances of Composite Laminated Beams - Xiangjun Lan; Zhihua Feng; Fan Lv (Shock and Vibration, 2014)
This paper presents a detailed study on the stochastic stability, jump, and bifurcation of the motion of the composite laminated beams subject to axial load. The largest Lyapunov exponent which determines the almost sure stability of the trivial solution is quantificationally resolved and the results show that the increase of the bandwidth facilitates the almost sure stability of the trivial response. The stochastic jump and bifurcation of the response are numerically calculated through the stationary joint probability and the results reveal that (a) the higher the excitation frequency is, the more probable the jump from the stable stationary nontrivial solution to the stable stationary trivial one is; (b) the most probable motion is around the nontrivial solution when the bandwidth is smaller; (c) the outer flabellate peak decreases, while the central volcano peak increases as the value of the excitation load decreases; and (d) the overall tendency of the response is that the probable motion jumps from the stable stationary nontrivial branch to the stable stationary trivial one as the fiber orientation angle of the first lamina with respect to the x-axis of the beam increases from zero to a smaller angle.